Організація збереження інформації в системі визначення виникнення м’язового тремору після анестезії у дітей - Висоцька, О. В.; Овченко, А. С.; Добродня, Г. С. (ХНУРЕ, 2018)
Tremor is a complex process that covers both central and peripheral mechanisms. The central mechanisms are associated with the synchronous oscillation of the cells of the nervous structures involved in providing the movement. he appearance of muscle tremor can significantly impair the conditions for conducting traditional post-operative monitoring. The gold standard of prophylaxis and resection of postoperative muscle tremor is still unclear, so the development of information technology to determine the occurrence of muscle tremor after anesthesia in children with congenital pathologies of the locomotor system is relevant today.
Keywords: спінальна анестезія; м’язовий тремор; патології опорно-рухового апарату